Cross-National Advertising and Behavioral Intentions: A Multilevel Analysis. Issue 1 (March 2014) - Walsh, Gianfranco; Shiu, Edward; Hassan, Louise M.
Previous research has provided limited insight into (1) the cross-national effectiveness of marketing communication aimed at engaging consumers and (2) the moderating role of national characteristics. This study assesses the effectiveness of a cross-national advertising campaign in terms of changing behavioral intentions. The authors examine the moderating effects of country-level indicators representing three institutional pillars (regulative, normative/moral, and cultural-cognitive) on the mediated associations between three advertising persuasion measures (message comprehension, attitude toward the campaign, and message elaboration) and behavioral intentions. The authors examine a multilevel analysis using survey data related to a 25-country advertising campaign to test hypothesized within-country and between-country effects. The results show that message comprehension affects message elaboration less strongly in countries with stronger regulative, normative/moral, and cultural-cognitive pillars. Attitude toward the campaign affects message elaboration less strongly in countries with stronger normative/moral and cultural-cognitive pillars. Message elaboration affects behavioral intention less strongly in countries with a stronger regulative pillar but more strongly in countries with a stronger normative/moral pillar. The authors discuss implications for international marketing theory and practice.